2021
DOI: 10.1073/pnas.2025094118
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a far-red–sensing cyanobacteriochrome reveals an atypical bilin conformation and spectral tuning mechanism

Abstract: Cyanobacteriochromes (CBCRs) are small, linear tetrapyrrole (bilin)-binding photoreceptors in the phytochrome superfamily that regulate diverse light-mediated adaptive processes in cyanobacteria. More spectrally diverse than canonical red/far-red–sensing phytochromes, CBCRs were thought to be restricted to sensing visible and near UV light until recently when several subfamilies with far-red–sensing representatives (frCBCRs) were discovered. Two of these frCBCRs subfamilies have been shown to incorporate bilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 79 publications
3
24
0
Order By: Relevance
“…Similarly, the distances between RcaE and Slr1393 with respect to the representative PCB atoms range from 3.2 to 5.1 Å. Recently, Bandara et al reported the far-red-absorbing state of the 2551g3 of far-red/orange CBCR subfamily (25), whose GAF domain shows high sequence similarity to that of RcaE. The Pfr dark state of 2551g3 adopts all syn conformation and all Z configuration but also shows a clockwise-rotated location of PCB similar to that seen in RcaE (25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the distances between RcaE and Slr1393 with respect to the representative PCB atoms range from 3.2 to 5.1 Å. Recently, Bandara et al reported the far-red-absorbing state of the 2551g3 of far-red/orange CBCR subfamily (25), whose GAF domain shows high sequence similarity to that of RcaE. The Pfr dark state of 2551g3 adopts all syn conformation and all Z configuration but also shows a clockwise-rotated location of PCB similar to that seen in RcaE (25).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bandara et al reported the far-red-absorbing state of the 2551g3 of far-red/orange CBCR subfamily (25), whose GAF domain shows high sequence similarity to that of RcaE. The Pfr dark state of 2551g3 adopts all syn conformation and all Z configuration but also shows a clockwise-rotated location of PCB similar to that seen in RcaE (25). The key interactions contributing to the location of PCB in the GAF domain of RcaE are hydrogen bonds and/or ion pairs between the carboxylates of the propionic acid of the B-ring and C-ring (hereafter called B-carboxylate and C-carboxylate, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible role of GUN4 is to maintain the lowest-energy conformation, and thus preventing photoisomerization as observed in a cyanobacterial photoreceptor that has an atypical PCB chromophore. 31 The function of the N-terminal domain conserved in cyanobacterial and algal GUN4 remains unclear. Its αA-αE arrange like the armadillo-repeats, which are often found to be involved in protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the ZZZsss conformer fits better into the binding pocket than the more rigid porphyrin (Figures 2c and 4b). One possible role of GUN4 is to maintain the lowest‐energy conformation, and thus preventing photoisomerization as observed in a cyanobacterial photoreceptor that has an atypical PCB chromophore 31 . The function of the N‐terminal domain conserved in cyanobacterial and algal GUN4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%